REVIEW OF THE USE OF DNA BARCODING IN AVIFAUNA RESEARCH: CONSERVATION, AUTHENTIFICATION, AND DISEASE DETECTION - I Wayan Rosiana; Made Pharmawati; I Made Murna; Putu Angga Wiradana; Ni Wayan Ayu Wiartini; Fransiskus Jimmy Roga (Universitas Airlangga, 2025)
DNA barcoding is an effective tool for identifying species, with additional uses for measuring molecular diversity, authentication of illegal products, and early detection of disease types. In this review, we discussed the use of DNA barcoding for Avifauna research, that is known to have an important impact on environmental health. The existence of Avifauna is threatened with extinction due to human anthropogenic activities. This review starts by providing a general overview of DNA barcoding, focusing on its application in Avifauna research, metabarcoding, as a tool in detecting food samples from the Avifauna, tracking enandgered and protected exotic birds, and tracking avifauna diseases. This review concludes with definitive statements and challenges regarding the use of DNA barcoding, especially in regions with high levels of avifauna diversity. This review can contribute to a better understanding of DNA barcoding and its potential in managing Avifauna genetic resources in the wild and conservation institutions.